Effects of capture and marking on the behaviour of moulting Pink-footed Geese Anser brachyrhynchus on Svalbard - Clausen, Kevin K.; Schreven, Kees H.T.; Madsen, Jesper (Wildfowl, 2020)
Tracking of individuals is increasingly being used in waterfowl research. However, the effects of capture and tags on waterfowl welfare and ecology are poorly understood and too rarely reported. In this paper, time budget data are used to investigate the behavioural effects of capture and marking on moulting and brood-rearing Pink-footed Geese Anser brachyrhynchus on their arctic breeding grounds. The study compares the prevalence of self-maintenance and foraging time for unringed/uncaptured birds, male birds marked with standard neck collars and female birds marked with heavier GPS collars, and reports on the reduction through time in the pecking behaviour directed towards these markers. Results indicate that capture and marking substantially altered behaviour of marked birds in the days immediately after capture, but also that this effect faded quickly and was not discernible after six days since marking. Proportions of time spent preening during foraging bouts indicated that in the first six days, GPS-collared birds were significantly more impacted (time preening ≈ 12%) than birds ringed with standard neck collars (≈ 3%). Both groups showed higher proportions of self-maintenance type behaviours than unringed birds of the same sex (time preening < 1%). The probability of an individual goose pecking its marker during an observation period was initially high for GPS-collared birds (≈ 65%), but decreased substantially to reach ≈ 2% by 11 days after capture. Our study indicates that, after an initial period of discomfort, neck collars and GPS collars are suitable for studying the behaviour of individual geese.